2016
DOI: 10.1002/eji.201546263
|View full text |Cite
|
Sign up to set email alerts
|

Free fatty acids sensitize dendritic cells to amplify TH1/TH17‐immune responses

Abstract: Obesity is associated with body fat gain and impaired glucose metabolism. Here, we identified both body fat gain in obesity and impaired glucose metabolism as two independent risk factors for increased serum levels of free fatty acids (FFAs). Since obesity is associated with increased and/or delayed resolution of inflammation observed in various chronic inflammatory diseases such as psoriasis, we investigated the impact of FFAs on human monocyte-derived and mouse bone marrow-derived dendritic cell (DCs) functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 69 publications
5
62
0
1
Order By: Relevance
“…Several studies have indicated the ability of free fatty acids to modulate DC differentiation and responses to LPS [9, 4446]. However, the direct effect of PA on dendritic cell activation and maturation is unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated the ability of free fatty acids to modulate DC differentiation and responses to LPS [9, 4446]. However, the direct effect of PA on dendritic cell activation and maturation is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…IL-1β supports the development of Th17 cells [79, 80], and Th17 cells have recently been implicated as a predominant driver of inflammation in human T1D and T2D [81]. In mice, PA primes MoDCs to generate Th1/Th17 responses upon LPS stimulation [44]. This study found no direct effect of PA on human MoDCs, likely due to too short of a treatment time for PA, a weak TLR4 agonist as we have demonstrated here.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not include these adipokines in this study, they could relate to the pathogenesis of the overweight patients with RA. Furthermore, free fatty acid also sensitizes dendritic cells to induce Th17 response, and could be a possible mediator in RA pathogenesis [23]. These points will be addressed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is associated with low-grade chronic inflammation due to deregulation of immune response. Enlarged adipocytes change their secretion pattern into releasing more pro-inflammatory mediators [32]. Accumulating data suggest that reciprocal interactions between the metabolic disturbances and immune system may be a link between the pathogenesis of psoriasis and obesity.…”
Section: Introductionmentioning
confidence: 99%